Preparation method and application of flower-like sulfur-doped zinc oxide gas-sensitive material for rapidly and nondestructively detecting methamphetamine
By preparing flower-like sulfur-doped zinc oxide gas-sensitive materials, the problem of sample pretreatment, high cost and time-consuming in the existing methamphetamine detection methods is solved, and the rapid and real-time detection of methamphetamine is achieved, with high sensitivity and Stability, suitable for drug monitoring.
Patent Information
- Application Number
- CN202411270563.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
The existing methamphetamine detection methods require sample pre-processing, are costly, cannot be tested in real time, and take a long time, which cannot meet the needs of fast and real-time monitoring.
Using a preparation method of a flower-like sulfur-doped zinc oxide gas-sensitive material for rapid non-destructive detection of methamphetamine, the precursor solution is obtained by mixing zinc nitrate with thiourea and reacting at a specific temperature, and then heat treatment is performed at a high temperature. A floral sulfur-doped zinc oxide gas-sensitive material is formed as a gas-sensitive element for detecting volatile gases of methamphetamine.
It realizes rapid and real-time detection of methamphetamine at lower operating temperatures, with high sensitivity, rapid response and stability, avoids sample pretreatment steps, and is suitable for drug detection and monitoring.
Smart Images

Figure CN119118187A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a gas-sensitive material. Background Art
[0002] In recent years, the proportion of new drugs that can be chemically synthesized (methamphetamine-ice) in drug cases has been increasing, and the harm caused to society has also increased. How to detect and monitor new drugs has become an important issue in drug control. From the perspective of social stability and personal safety, rapid detection and real-time monitoring of methamphetamine (ice) are of great significance to maintaining social security and human health. At present, there are many methods for detecting methamphetamine (ice), including high performance liquid chromatography, gas chromatography-mass spectrometry, solid phase extraction and capillary electrophoresis. However, due to the poor volatility of solid targets, most of these methods require the sample to be processed into a solution before measurement, which is costly, cannot be detected in real time, and takes a long time.
[0003] Therefore, developing a new type of chemical resistance gas sensor with high responsiveness, good selectivity and fast response speed to detect trace vapors emitted by methamphetamine (ice) will be convenient for supervisors to carry and use in some special application places. Summary of the invention
[0004] The present invention aims to solve the problems in existing methamphetamine detection methods, such as the need for sample pretreatment, high cost, inability to detect in real time, and long time consumption, and to provide a preparation method and application of a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid and non-destructive detection of methamphetamine.
[0005] A method for preparing a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid non-destructive detection of methamphetamine is carried out according to the following steps:
[0006] 1. Mix zinc nitrate and thiourea, then add them into a solvent to dissolve to obtain a mixed solution, and react the mixed solution at a temperature of 140° C. to 200° C. for 4 h to 10 h to obtain a precursor solution;
[0007] The concentration of zinc nitrate in the mixed solution is 0.36 mol / L to 0.80 mol / L;
[0008] 2. The precursor solution is centrifuged, washed and dried, and then heat-treated for 2h to 4h in an air atmosphere at a temperature of 600°C to 800°C to obtain a flower-shaped sulfur-doped zinc oxide gas-sensitive material.
[0009] The invention discloses an application of a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid and non-destructive detection of methamphetamine. Under the condition of a working temperature of 100° C. to 180° C., the material is used as a gas-sensitive element to detect methamphetamine.
[0010] The beneficial effects of the present invention are:
[0011] The present invention adopts a simple one-step hydrothermal method to synthesize flower-shaped sulfur-doped zinc oxide gas-sensitive materials. The operation process is simple and efficient and can be mass-produced. The prepared flower-shaped sulfur-doped zinc oxide gas-sensitive materials successfully dope S atoms into the ZnO lattice. This result increases the Lewis base sites in the material and produces cation defects, which improves the conductivity of the material and effectively reduces the operating temperature of the sensor. At the same time, the special porous flower-shaped structure of the material also provides a large specific surface area (16.39 m 2 ·g -1 ), which is beneficial to improve the gas-sensing properties of the material.
[0012] The flower-shaped sulfur-doped ZnO nanomaterial prepared by the present invention is assembled into a sensitive element, and the volatile gas of methamphetamine (ice) is detected by the method of testing gas saturated vapor, and the trace vapor volatilized by methamphetamine (ice) is monitored in real time. The sensor can effectively detect the low-concentration saturated vapor volatilized by solid samples, has good sensitivity characteristics (sensitivity of 7.81) at 130°C, responds quickly (response time is less than 30 seconds) and has good stability (sensitivity change is less than 1.68% when measured within 60 days), can be reused, and has high selectivity. Utilizing this performance of the material, simple real-time detection of methamphetamine (ice) can be carried out, avoiding the pretreatment process of the previous detection process, and may be applied to activities such as drug crime control in the future, which is conducive to rapid identification and detection of drugs and prevents drugs from entering the market.
[0013] The invention discloses a preparation method and application of a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid and nondestructive detection of methamphetamine. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a scanning electron microscope image of the precursor described in step 2 of Example 1, where a is a scale of 2 μm and b is a scale of 1 μm;
[0015] Figure 2 This is a scanning electron microscope image of the flower-shaped sulfur-doped zinc oxide gas-sensitive material prepared in step 2 of Example 1, where a is a scale of 2 μm and b is a scale of 1 μm;
[0016] Figure 3 This is the SEM image of the precursor described in step 2 of comparative experiment 1, a is the scale 2 μm, b is the scale 1 μm;
[0017] Figure 4 This is the scanning electron microscope image of the zinc oxide gas-sensitive material prepared in step 2 of comparative experiment 1. a is a scale of 2 μm, and b is a scale of 1 μm;
[0018] Figure 5 XRD patterns of the flower-shaped sulfur-doped zinc oxide gas-sensitive material prepared in step 2 of Example 1 and the zinc oxide gas-sensitive material prepared in comparative experiment 1, a is the full spectrum, b is Figure 5 A partial enlarged view in a;
[0019] Figure 6 This is a specific surface area diagram of the flower-shaped sulfur-doped zinc oxide gas-sensitive material prepared in step 2 of Example 1;
[0020] Figure 7 This is a cation defect test diagram of the flower-shaped sulfur-doped zinc oxide gas-sensitive material prepared in step 2 of Example 1;
[0021] Figure 8 The sensitivity of the flower-shaped sulfur-doped ZnO nanomaterial gas sensor prepared in Example 2 and the ZnO nanomaterial gas sensor prepared in Comparative Experiment 2 to different solid powder vapors;
[0022] Fig. 9 This is the response recovery curve of the flower-shaped sulfur-doped ZnO nanomaterial gas sensor prepared in Example 2 to methamphetamine;
[0023] Fig.10 This is a stability test curve of the flower-shaped sulfur-doped ZnO nanomaterial gas sensor prepared in Example 2 to methamphetamine. DETAILED DESCRIPTION
[0024] Specific implementation method 1: This implementation method is a preparation method of a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid non-destructive detection of methamphetamine, which is carried out according to the following steps:
[0025] 1. Mix zinc nitrate and thiourea, then add them into a solvent to dissolve to obtain a mixed solution, and react the mixed solution at a temperature of 140° C. to 200° C. for 4 h to 10 h to obtain a precursor solution;
[0026] The concentration of zinc nitrate in the mixed solution is 0.36 mol / L to 0.80 mol / L;
[0027] 2. The precursor solution is centrifuged, washed and dried, and then heat-treated for 2h to 4h in an air atmosphere at a temperature of 600°C to 800°C to obtain a flower-shaped sulfur-doped zinc oxide gas-sensitive material.
[0028] The flower-shaped sulfur-doped zinc oxide gas-sensitive material in this specific embodiment needs to break the CC bond to react with methamphetamine (ice), and the CC bond energy is 345.6 KJ / mol, which means that methamphetamine is difficult to react with the material. However, this specific embodiment can detect methamphetamine at a lower working temperature, which is attributed to the special structure of the flower-shaped sulfur-doped zinc oxide nanomaterial in this specific embodiment, rich cation defects and large specific surface area.
[0029] Methamphetamine shows Lewis acid properties. This specific embodiment effectively increases the Lewis base sites in the material by designing the synthesis of the material, adjusting the material electronic structure and the method of lattice defects, and increasing the Lewis base sites on the surface of the material can improve the adsorption capacity of the material to methamphetamine vapor. For ZnO materials, S atoms can be successfully doped into the lattice of ZnO to increase the Lewis base sites in the material by introducing transition metal sulfides and calcining at high temperature. S atoms and O atoms belong to the same main group, but S atoms have stronger ability to accept electrons, so that stronger forces can be generated between them and transition metal atoms. In addition, S atoms have larger diameters and stronger electronegativity. Therefore, S-doped ZnO is prone to lattice distortion, which causes defects in the material and changes conductivity, thereby reducing the operating temperature of the sensor and improving the sensing performance of the material.
[0030] The beneficial effects of this specific implementation are:
[0031] In this specific embodiment, a simple one-step hydrothermal method is used to synthesize the flower-shaped sulfur-doped zinc oxide gas-sensitive material. The operation process is simple and efficient and can be mass-produced. The prepared flower-shaped sulfur-doped zinc oxide gas-sensitive material successfully doped S atoms into the ZnO lattice. This result increases the Lewis base sites in the material and produces cation defects, which improves the conductivity of the material and effectively reduces the operating temperature of the sensor. At the same time, the special porous flower-shaped structure of the material also provides a large specific surface area (16.39 m 2 ·g -1 ), which is beneficial to improve the gas-sensing properties of the material.
[0032] The flower-shaped sulfur-doped ZnO nanomaterial prepared by this specific embodiment is assembled into a sensitive element, and the volatile gas of methamphetamine (ice) is detected by the method of testing gas saturated vapor, and the trace vapor volatilized by methamphetamine (ice) is monitored in real time. The sensor can effectively detect the low-concentration saturated vapor volatilized by solid samples, and has good sensitivity characteristics (sensitivity is 7.81) at 130 ℃ to methamphetamine (ice) vapor, rapid response (response time is less than 30 seconds) and good stability (sensitivity change is less than 1.68% when measured within 60 days), reusable, and has high selectivity. Utilizing this performance of the material, simple real-time detection of methamphetamine (ice) can be carried out, avoiding the pretreatment process of the previous detection process, and may be applied to activities such as drug crime control in the future, which is conducive to rapid identification and detection of drugs and preventing drugs from entering the market.
[0033] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the mass ratio of zinc nitrate to thiourea in step 1 is (3-5): 1. The rest is the same as specific embodiment 1.
[0034] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that the solvent in step 1 is a mixed solvent of ethylenediamine and water, and the volume ratio of ethylenediamine to water is (5-9): 1. Others are the same as specific embodiment 1 or 2.
[0035] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 1, the temperature is raised to 140° C. to 200° C. at a heating rate of 5° C. / min to 10° C. / min. The rest is the same as specific embodiments 1 to 3.
[0036] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step 2, the temperature is raised to 600° C. to 800° C. at a heating rate of 5° C. / min to 10° C. / min. The rest is the same as specific embodiments 1, 2 to 4.
[0037] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: in step 2, centrifugation is performed at a speed of 4000 r / min to 8000 r / min for 1 min to 3 min, and then the mixture is washed with deionized water and anhydrous ethanol respectively, and finally dried at a temperature of 60° C. to 120° C. for 6 h to 24 h. The rest is the same as specific embodiments 1 to 5.
[0038] Specific embodiment seven: This embodiment is an application of a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid and non-destructive detection of methamphetamine. Under the condition of an operating temperature of 100°C to 180°C, it is used as a gas-sensitive element to detect methamphetamine.
[0039] Specific embodiment eight: This embodiment differs from specific embodiment seven in that the gas sensor is prepared according to the following steps:
[0040] The flower-shaped sulfur-doped zinc oxide gas-sensitive material is mixed with pine alcohol to form a slurry, and then the slurry is coated on the surface of a carrier having two metal electrodes, first dried at a temperature of 70°C to 90°C, and then heat treated at a temperature of 260°C to 320°C for 0.5h to 1.5h, and finally a heating device is placed on the electrode to obtain a flower-shaped sulfur-doped ZnO nanomaterial gas-sensitive element. The rest is the same as the specific embodiment seven.
[0041] Specific implementation method 9: This implementation method is different from specific implementation method 7 or 8 in that the mass percentage of terpineol in the slurry is 5% to 10%. The rest is the same as specific implementation method 7 or 8.
[0042] Specific embodiment 10: This embodiment differs from any one of specific embodiments 7 to 9 in that the coating amount is 0.05 mg / cm 2 ~0.10mg / cm 2 The slurry is coated on the surface of a carrier having two metal electrodes; the carrier is a ceramic tube, a ceramic tube sheet, a silicon wafer, a circuit board or an interdigitated electrode. The rest is the same as the specific embodiments 7 to 9.
[0043] The following examples are used to verify the beneficial effects of the present invention:
[0044] Embodiment 1:
[0045] A method for preparing a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid non-destructive detection of methamphetamine is carried out according to the following steps:
[0046] 1. Mix zinc nitrate and thiourea, then add them into a solvent to dissolve to obtain a mixed solution, heat the mixed solution to 140° C. at a heating rate of 10° C. / min, and react the mixed solution at 140° C. for 8 hours to obtain a precursor solution;
[0047] The concentration of zinc nitrate in the mixed solution is 0.5 mol / L;
[0048] 2. Centrifuge the precursor solution at a rotation speed of 6000r / min for 2min, then wash it with deionized water and anhydrous ethanol respectively, and then dry it at a temperature of 70°C for 12h to obtain a precursor, and then increase the temperature of the precursor to 700°C at a heating rate of 7°C / min, and heat treat it at 700°C in an air atmosphere for 2h to obtain a flower-shaped sulfur-doped zinc oxide gas-sensitive material, abbreviated as S-ZnO.
[0049] The mass ratio of zinc nitrate to thiourea described in step 1 is 4:1.
[0050] The solvent described in step 1 is a mixed solvent of ethylenediamine and water, and the volume ratio of ethylenediamine to water is 7:1.
[0051] Comparative Experiment 1: The difference between this comparative experiment and Example 1 is that: the addition of thiourea in step 1 is eliminated; the volume ratio of ethylenediamine to water in step 1 is 3:1; and zinc oxide gas-sensitive material, abbreviated as ZnO, is obtained in step 2. The rest is the same as Example 1.
[0052] Figure 1 This is a scanning electron microscope image of the precursor described in step 2 of Example 1, where a is a scale of 2 μm and b is a scale of 1 μm. It can be seen from the figure that the product is a flower-like structure composed of smooth nanosheets with a diameter of about 5.53 μm to 7.64 μm.
[0053] Figure 2 This is a scanning electron microscope image of the flower-shaped sulfur-doped zinc oxide gas-sensitive material prepared in step 2 of Example 1, where a is a scale of 2 μm and b is a scale of 1 μm. It can be seen from the figure that after high-temperature calcination, the sample can still maintain its flower-like structure, and a large number of pores appear on the surface of the nanosheets, with a diameter of still 5.53 μm to 7.64 μm, but the generation of a large number of pores is conducive to the adsorption of gas molecules.
[0054] Figure 3 This is the SEM image of the precursor described in step 2 of comparative experiment 1, a is the scale 2 μm, b is the scale 1 μm; Figure 4 The scanning electron microscope image of the zinc oxide gas-sensitive material prepared in step 2 of comparative experiment 1, a is a scale of 2μm, b is a scale of 1μm; it can be seen from the figure that the morphology of the product without adding thiourea is also nanosheets, but it cannot be assembled into a flower-like structure, and the morphology of the nanosheets is difficult to maintain after firing, and it becomes a morphology of particle accumulation.
[0055] Figure 5 XRD patterns of the flower-shaped sulfur-doped zinc oxide gas-sensitive material prepared in step 2 of Example 1 and the zinc oxide gas-sensitive material prepared in comparative experiment 1, a is the full spectrum, b is Figure 5 The local enlarged image in a; it can be seen from the figure that after adding thiourea during the reaction process, the diffraction peak position of the product shifts significantly, indicating that sulfur is successfully doped into the ZnO lattice.
[0056] Figure 6 The specific surface area of the flower-shaped sulfur-doped zinc oxide gas-sensitive material prepared in step 2 of Example 1 is shown in the figure. As can be seen from the figure, the flower-shaped sulfur-doped zinc oxide has a large specific surface area (16.39 m 2 ·g -1 ), which provides more active sites for the adsorption of methamphetamine gas. Therefore, the material has good gas-sensing properties.
[0057] Figure 7 This is a cation defect test diagram of the flower-shaped sulfur-doped zinc oxide gas-sensitive material prepared in step 2 of Example 1; as can be seen from the figure, the material contains abundant cation defects, and the presence of cation defects can effectively reduce the conductivity of the material, so that the sensitive material has a lower test temperature.
[0058] Embodiment 2:
[0059] The gas sensing element is prepared by using the flower-shaped sulfur-doped zinc oxide gas sensing material of Example 1, specifically by the following steps:
[0060] The flower-shaped sulfur-doped zinc oxide gas-sensitive material was mixed with pinene alcohol to form a slurry, and then the coating amount was 0.07 mg / cm 2 The slurry is coated on the surface of a carrier having two metal electrodes, first dried at 80°C, then heat treated at 300°C for 1h, and finally a heating device is placed on the electrode to obtain a flower-shaped sulfur-doped ZnO nanomaterial gas sensor.
[0061] The mass percentage of terpineol in the slurry is 6%.
[0062] The carrier is a ceramic tube.
[0063] After the flower-shaped sulfur-doped ZnO nanomaterial gas sensor is aged and stabilized, the gas-sensing performance is tested. The detection method is implemented according to the following steps: the gas is tested at a temperature of 130°C using a static test method. Methamphetamine, soda, monosodium glutamate, flour, sugar, salt or a solid powder mixture (the mass ratio of methamphetamine: soda: monosodium glutamate: flour: sugar: salt is 1:1:1:1:1:1) is placed in different clean wide-mouth bottles, and naturally evaporated at room temperature to obtain saturated vapor. During the test, the gas sensor is first placed in the air to stabilize for a period of time to reach a constant value, and then the sensor is quickly placed in the gas chamber. After the resistance drops to a stable value, the sensor is taken out and the sensor returns to the initial resistance in the air. The sensitivity of the sensor to the target gas is defined as: S = Ra / Rg, the resistance of the sensor in the air is Ra, and the resistance in the gas is Rg. The response time to gas adsorption is the time required for the resistance value of the device to drop to 90% (Ra-Rg) after being exposed to the target gas. The recovery time is the time required for the resistance of the device to recover to 90% (Ra-Rg) after desorption.
[0064] Comparative Experiment 2: This comparative experiment is different from Example 2 in that the flower-shaped sulfur-doped zinc oxide gas-sensitive material prepared in Example 1 is replaced with the zinc oxide gas-sensitive material prepared in Comparative Experiment 1 to obtain a ZnO nanomaterial gas-sensitive element. The rest is the same as Example 1.
[0065] Figure 8The flower-shaped sulfur-doped ZnO nanomaterial gas sensor prepared in Example 2 and the sensitivity of the ZnO nanomaterial gas sensor prepared in Comparative Experiment 2 to different solid powder vapors; As can be seen from the figure, the flower-shaped sulfur-doped ZnO nanomaterial gas sensor has good gas-sensitive performance for methamphetamine vapor at 130°C, with a response sensitivity of 7.81, and shows good selectivity for different solid powder vapors. At the same time, the detection results of mixed vapors of different solid powders also show that the flower-shaped sulfur-doped ZnO nanomaterial gas sensor has excellent anti-interference performance, and can effectively identify methamphetamine vapor in different vapors, with a response sensitivity of 7.76; while for the ZnO nanomaterial gas sensor prepared in Comparative Experiment 2, at the same working temperature of 130°C, ZnO can only detect methamphetamine vapor at 2.80, which is significantly reduced compared to the sulfur-doped zinc oxide sensitive material, indicating that the flower-shaped sulfur-doped zinc oxide synthesized by the method can effectively improve the selectivity of methamphetamine vapor.
[0066] Fig. 9 This is the response recovery curve of the flower-shaped sulfur-doped ZnO nanomaterial gas sensor to methamphetamine prepared in Example 2; as can be seen from the figure, the flower-shaped sulfur-doped ZnO nanomaterial gas sensor has good reproducibility to methamphetamine vapor at 130°C, the response time to methamphetamine vapor is less than 30s, the recovery time is less than 900s, and the initial resistance can be restored after five consecutive tests, and the relative standard deviation of the five tests is 1.73%.
[0067] The flower-shaped sulfur-doped ZnO nanomaterial gas sensor prepared in Example 2 was tested again every 10 days after the first test, and the test was continued for 60 days. After each test, the sensitive material was placed in an air environment for storage; Fig.10 This is a stability test curve of the flower-shaped sulfur-doped ZnO nanomaterial gas sensor prepared in Example 2 to methamphetamine; as can be seen from the figure, the sensor can maintain good gas-sensitive performance to methamphetamine vapor within 60 days, and the relative standard deviation is 1.68%.
Claims
1. A method for preparing a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid nondestructive detection of methamphetamine, characterized in that It is carried out in the following steps:
1. Mix zinc nitrate and thiourea, then add them into a solvent to dissolve to obtain a mixed solution, and react the mixed solution at a temperature of 140° C. to 200° C. for 4 h to 10 h to obtain a precursor solution; The concentration of zinc nitrate in the mixed solution is 0.36 mol / L to 0.80 mol / L; 2. The precursor solution is centrifuged, washed and dried, and then heat-treated for 2h to 4h in an air atmosphere at a temperature of 600°C to 800°C to obtain a flower-shaped sulfur-doped zinc oxide gas-sensitive material.
2. The method for preparing a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid nondestructive detection of methamphetamine according to claim 1, characterized in that The mass ratio of zinc nitrate to thiourea described in step 1 is (3-5):
1.
3. The method for preparing a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid nondestructive detection of methamphetamine according to claim 1, characterized in that The solvent described in step 1 is a mixed solvent of ethylenediamine and water, and the volume ratio of ethylenediamine to water is (5-9):
1.
4. The method for preparing a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid nondestructive detection of methamphetamine according to claim 1, characterized in that In step 1, the temperature is raised to 140°C to 200°C at a heating rate of 5°C / min to 10°C / min.
5. The method for preparing a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid nondestructive detection of methamphetamine according to claim 1, characterized in that In step 2, the temperature is raised to 600° C. to 800° C. at a heating rate of 5° C. / min to 10° C. / min.
6. The method for preparing a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid nondestructive detection of methamphetamine according to claim 1, characterized in that In step 2, centrifugation is performed at a rotation speed of 4000 r / min to 8000 r / min for 1 min to 3 min, and then washed with deionized water and anhydrous ethanol respectively, and finally dried at a temperature of 60° C. to 120° C. for 6 h to 24 h.
7. Application of a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid nondestructive detection of methamphetamine prepared as claimed in claim 1, characterized in that Under the condition of working temperature of 100℃~180℃, it is used as a gas sensor to detect methamphetamine.
8. The use of a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid nondestructive detection of methamphetamine according to claim 7, characterized in that The gas sensor is specifically prepared according to the following steps: The flower-shaped sulfur-doped zinc oxide gas-sensitive material is mixed with pine oil to form a slurry, and then the slurry is coated on the surface of a carrier with two metal electrodes, first dried at a temperature of 70°C to 90°C, and then heat treated at a temperature of 260°C to 320°C for 0.5h to 1.5h, and finally a heating device is placed on the electrode to obtain a flower-shaped sulfur-doped ZnO nanomaterial gas-sensitive element.
9. The use of a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid nondestructive detection of methamphetamine according to claim 8, characterized in that The mass percentage of terpineol in the slurry is 5% to 10%.
10. The use of a flower-shaped sulfur-doped zinc oxide gas-sensitive material for rapid non-destructive detection of methamphetamine according to claim 8, characterized in that The coating amount is 0.05mg / cm 2 ~0.10mg / cm 2 The slurry is coated on the surface of a carrier having two metal electrodes; the carrier is a ceramic tube, a ceramic tube sheet, a silicon sheet, a circuit board or an interdigitated electrode.
